2012
DOI: 10.1039/c2cp40595d
|View full text |Cite
|
Sign up to set email alerts
|

Initial solid electrolyte interphase formation process of graphite anode in LiPF6 electrolyte: an in situ ECSTM investigation

Abstract: Understanding the structure and formation dynamics of the solid electrolyte interphase (SEI) on the electrode/electrolyte interface is of great importance for lithium ion batteries, as the properties of the SEI remarkably affect the performances of lithium ion batteries such as power capabilities, cycling life, and safety issues. Herein, we report an in situ electrochemical scanning tunnelling microscopy (ECSTM) study of the surface morphology changes of a highly oriented pyrolytic graphite (HOPG) anode during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 60 publications
2
30
0
Order By: Relevance
“…Since the basal plane contains natural defects such as grain boundaries and step edges already before charging, Li + intercalation occurred also through these defects of the basal plane. Graphite exfoliation is known to occur at edge planes of HOPG during charging . In addition, Campana et al .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Since the basal plane contains natural defects such as grain boundaries and step edges already before charging, Li + intercalation occurred also through these defects of the basal plane. Graphite exfoliation is known to occur at edge planes of HOPG during charging . In addition, Campana et al .…”
Section: Resultssupporting
confidence: 85%
“…Since the basal plane contains natural defects such as grain boundaries and step edges alreadyb efore charging, Li + intercalationo ccurreda lso through these defects of the basal plane.G raphite exfoliation is knownt o occur at edge planes of HOPG during charging. [28][29][30] In addition, Campana et al [25] observed graphite exfoliatione ven at structural defects of the basal plane.H ence,t he area ratio between edge and basal planes increased significantly during lithiationa nd the basal plane contained ah igh fractiono f edge planes after charging. This is evident from Figure 1b, which shows macroscopic topographic changes after lithiation, which can be explained by large cracks of the graphene layers due to volume expansiond uring lithiation.…”
Section: Resultsmentioning
confidence: 99%
“…This leads to a reversibility of 0.8 Li, close to one Li expected for the full conversion of AlLi. Therefore, the reaction path can be described as the conversion reaction of AlH 3 into LiH and Al followed by 20 the alloying reaction of Al with Li. The lithiation/delithiation of aluminium is the primary contributor to the reversible capacity beyond the first cycle however, it should be noted that the formation of very small and non-oxidized Al particles allows a nearly complete (80%) reaction between AlLi and Li.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the height of the step was also strongly correlated to the initial exfoliation potential. When the potential was further reduced to 0.8–0.7 V versus Li/Li + , they observed the growth of clusters and flakes on the step edge (ascribed to the formation of ternary graphite intercalation compounds), the growth of small island clusters with poor conductivity on the terrace (attributed to the reduction product of EC), as well as the exfoliation of the graphite layers …”
Section: Spm Studies Of Negative Electrode Materials In Libsmentioning
confidence: 99%